Optimizing MSME Product Marketing Using the SOSTAC Method Through the Digital Study Platform in Blitar City - Subandi, Hendi; Nugraha, Adri Putra; Jazuli, A Muhamad; Munir, Misbakhul; Huda, Choirul (Jurnal Abdimas, 2025)
MSMEs in Blitar City still face difficulties in marketing. Globalization and digitalization require MSMEs to be able to compete competitively in the virtual market. This community service seeks to increase the literacy of MSMEs in Blitar City in implementing the SOSTAC method so that they can compete globally in their marketing. The method used is Participatory Rural Appraisal (PRA) to encourage active community involvement, in this case MSMEs with universities as facilitators. Based on the activities that have been carried out, it was found that MSMEs in general are still unfamiliar with digital platforms. The increase in literacy related to SOSTAC triggers MSMEs' awareness to strategize in marketing and explore the features on digital platforms more thoroughly so that this can have an impact on the engagement of online stores of MSMEs in Blitar City.